Analisis Strategi Pemasaran Hasil Hutan Bukan Kayu (Gondorukem) Perhutani Ke Pasar International - Albari, Albari; Akbar, Aqaeda Ramadhana Al rasyid (J-MAS (Jurnal Manajemen dan Sains), 2024)
Researchers examined a company operating in the forestry sector that sells forestry products to the international market. This research aims to analyze the company's marketing program using descriptive qualitative methods by collecting data through observation and in-depth interviews, secondary company data, and collecting documentation. This research produces an analysis of marketing strategies for forest products to international markets. This analysis is based on the theory of segmenting, targeting and positioning (STP) and mix marketing. It is hoped that the analysis that has been made by researchers can help companies to develop.